Optical coherence tomography angiography and progressive retinal nerve fiber layer loss in mild to moderate open-angle glaucoma - Zia Sultan Pradhan; Thanemozhi Srinivasan; Shruthi Sreenivasaiah; Dhanaraj AS Rao; Sujani Shroff; Sathi Devi; Carroll A B Webers; Harsha Laxmana Rao (PLoS ONE, 2025)
Purpose To evaluate the association between optical coherence tomography (OCT) angiography measurements and progressive retinal nerve fiber layer (RNFL) loss in eyes with mild to moderate open-angle glaucoma. Methods In this prospective study, 111 quadrants of 59 eyes with mild-moderate open-angle glaucoma were longitudinally evaluated for a minimum of 2 years with at least 3 OCT scans performed. OCT angiography was performed at baseline and vessel densities in the peripapillary and parafoveal regions were determined quadrant-wise. Effect of demographic (age, sex, presence of diabetes and hypertension), clinical (mean and fluctuation of intraocular pressure, presence of pseudoexfoliation, presence of disc hemorrhages, central corneal thickness, baseline mean deviation on visual fields) and OCT angiography parameters (peripapillary and parafoveal vessel densities) on rate of RNFL change was determined using linear mixed models. Results Average baseline hemifield mean deviation and quadrant RNFL thickness was -3.5 ±  2.5dB and 97 ± 18µm respectively. The mean follow-up duration was 5.0 ±  1.8 years. The rate of change of quadrant RNFL thickness (RNFL slope) was -1.67 ±  0.2 µm/year. Multivariate mixed models showed that presence of pseudoexfoliation deposits (co-efficient -0.78 ±  0.34, p = 0.025) and optic disc hemorrhages (co-efficient -0.59 ±  0.28, p = 0.040) were associated with a faster rate of RNFL decline. None of the baseline OCT angiography parameters evaluated in this study showed any association with the RNFL slope. Conclusions Presence of pseudoexfoliation and optic disc hemorrhages are significant risk factors for glaucoma progression in open-angle glaucoma. Baseline superficial vessel density, as measured on OCT angiography, was not associated with the rate of RNFL loss in mild-moderate open-angle glaucoma.